Peningkatan Kompetensi Profesi Guru Bahasa Arab Melalui Pelatihan Penulisan dan Publikasi Artikel Ilmiah Berbasis Open Journal System - Andri Ilham; Nuruddin; Mohamad Sarip; Samsi Setiadi (Universitas Lancang Kuning, 2022)
The requirement to write scientific articles is often still an obstacle to support the advancement of a teacher's career path. Generally they have difficulty fulfilling it because they have not been trained or even have never written and produced research work in the form of scientific articles. Therefore, teachers need to be given the training to improve professional competence through writing and publishing scientific articles. The purpose of this community service projects is to provide knowledge for Arabic teachers of Musyawarah Guru Mata Pelajaran (MGMP) in Banten Province who do not have direct experience in writing and publishing scientific articles in online journals through the Open Journal System (OJS) platform. The method of implementing this activity is carried out using the Zoom Meetings platform in a webinar format which includes presentation materials, questions and answers, and simulations. Meanwhile, the results of this activity showed a positive response from the teachers for the development of their competences in writing and publishing scientific articles. Persyaratan menulis artikel ilmiah kerap kali masih menjadi hambatan untuk menunjang kenaikan jenjang karir guru. Umumnya mereka mengalami kesulitan untuk memenuhinya karena memang belum terlatih atau bahkan sama sekali belum pernah menulis dan menghasilkan hasil penelitian berupa artikel ilmiah. Oleh karena itu, guru perlu diberikan pelatihan untuk meningkatkan kompetensi profesi melalui penulisan dan publikasi artikel ilmiah. Tujuan dari pengabdian ini adalah memberikan pengetahuan bagi guru, khususnya Musyawarah Guru Mata Pelajaran (MGMP) Bahasa Arab di Provinsi Banten yang belum mempunyai pengalaman langsung dalam menulis artikel ilmiah dan mempublikasikannya ke dalam jurnal melalui platform Open Journal System (OJS). Adapun metode penerapan kegiatan ini dilaksanakan dengan menggunakan platform zoom meetings dalam format webinar yang meliputi presentasi materi, tanya jawab, dan simulasi. Sementara itu, dari hasil kegiatan ini menunjukkan respon positif dari para guru untuk pengembangan kompetensi mereka dalam menulis dan mempublikasikan artikel ilmiah.